All-uses testing of shared memory parallel programs - Yang, Cheer-Sun D.; Pollock, Lori L. (Software testing, verification & reliability, 2003)
Parallelism has become a way of life for many scientific programmers. A significant challenge in bringing the power of parallel machines to these programmers is providing them with a suite of software tools similar to the tools that sequential programmers currently utilize. Unfortunately, writing correct parallel programs remains a challenging task.In particular, automatic or semi‐automatic testing tools for parallel programs are lacking. This paper takes a first step in developing an approach to providing all‐uses coverage for parallel programs. A testing framework and theoretical foundations for structural testing are presented, including test data adequacy criteria and hierarchy, formulation and illustration of all‐uses testing problems, classification of all‐uses test cases for parallel programs, and both theoretical and empirical results with regard to what can be achieved with all‐uses coverage for parallel programs. Copyright © 2003 John Wiley & Sons, Ltd.